Research on Application of Technology Using Water Jet on Machining of Polymeric Composite Biological-Reinforced Materials - Muller, Miroslav; Valasek, Petr; Kolar, Viktor (Manufacturing Technology Journal, 2018)
The paper deals with a machining of polymeric composite materials reinforced with fibres from hemp, false banana (Ensete ventricosum) and microparticles from Jatropha Curcas L. seedcakes by means of a technology using a water jet (abrasive water jet AWJ, water jet WJ). A matrix of the composite material is from a structural resin used for a production of sport equipment which shows good mechanical properties, but is it very brittle and it comes to its destruction during machining. Therefore, the water jet technology was used for the research. The research was focused on the evaluation of an influence of a velocity of a cutting head movement on a kerf width inlet and outlet the composite board by means of an optical analysis and on a connected quality of the cut. The composite material based on the biological reinforcement was cut by CNS cutting machine AWJ CT 0806 at a different velocity of the cutting head movement (traverse speed), i.e. 50, 250, 750 and 1000 mm/min. The research results proved a significant difference between the technologies AWJ and WJ and also among the velocities of the cutting head movement. The cut was inhomogeneous under unsuitable conditions and it came to a significant destruction of a surface outlet of the water jet.
Keywords: abrasive water jet; cut quality; false banana; hemp; jatropha curcas L.; water jet